A empregabilidade dos imigrantes haitianos no mercado de trabalho da cidade de Chapecó – SC - Senatus, Emilus (2019)
In recent years, manys Haitians have migrated to Brazil to find jobs to improve their economic conditions, some of which have sought the city of Chapecó in the state of Santa Catarina - Brazil. As you know, Haiti was the first free black people in the world, this small country of Central America, especially the Caribbean, gained independence since 1804, during which time the Haitian people faced great economic difficulties, political and natural catastrophes. The earthquake that struck Haiti on January 12, 2010 worsened economic conditions, motivating large numbers of Haitian citizens to migrate to Brazil. Taking into consideration the representativeness of Haitian immigrants in the Brazilian labor market and especially in the city of Chapecó, this research has as general objective to analyze the current conditions of employability of the Haitian immigrants in the labor market in this city. For this, a qualitative research was carried out, which is divided in two parts, the first phase is the bibliographical research and the second field research. For the field research, questionnaires were applied, which allowed the analysis of data from a sample of 136 participants. Thus, it was possible to identify the demographic profile of this sample, its distribution in the business sectors, aspects related to the remuneration of these immigrants and their professional training, among other issues. The conclusions that led to this research point to the difficulties encountered and the reality of the present moment of the Haitian immigrants in the city of Chapecó - SC.